Spreading depolarization causes reperfusion failure after cerebral ischemia - Törteli Anna; Tóth Réka; Berger Sarah; Samardzic Sarah; Bari Ferenc; Menyhárt Ákos; Farkas Eszter (2023)
Despite successful recanalization, reperfusion failure associated with poor neurological outcomes develops in half of treated stroke patients. We explore here whether spreading depolarization (SD) is a predictor of reperfusion failure. Global forebrain ischemia/reperfusion was induced in male and female C57BL/6 mice (n = 57). SD and cerebral blood flow (CBF) changes were visualized with transcranial intrinsic optical signal and laser speckle contrast imaging. To block SD, MK801 was applied (n = 26). Neurological deficit, circle of Willis (CoW) anatomy and neuronal injury were evaluated 24 hours later. SD emerged after ischemia onset in one or both hemispheres under a perfusion threshold (CBF drop to 21.1 ± 4.6 vs. 33.6 ± 4.4%, SD vs. no SD). The failure of later reperfusion (44.4 ± 12.5%) was invariably linked to previous SD. In contrast, reperfusion was adequate (98.9 ± 7.4%) in hemispheres devoid of SD. Absence of the P1 segment of the posterior cerebral artery in the CoW favored SD occurrence and reperfusion failure. SD occurrence and reperfusion failure were associated with poor neurologic function, and neuronal necrosis 24 hours after ischemia. The inhibition of SD significantly improved reperfusion. SD occurrence during ischemia impairs later reperfusion, prognosticating poor neurological outcomes. The increased likelihood of SD occurrence is predicted by inadequate collaterals.
Keywords: Általános orvostudomány